2014
DOI: 10.1074/jbc.m113.544460
|View full text |Cite
|
Sign up to set email alerts
|

Structural-Functional Analysis of the Third Transmembrane Domain of the Corticotropin-releasing Factor Type 1 Receptor

Abstract: Background:The molecular mechanisms underlying activation of CRF 1 receptor (CRF 1 R) were elusive. Results: We determined specific residues in the transmembrane domains (TMs) of CRF 1 R that are critical for receptor activation. Conclusion: A possible "transmission switch" involving TM interactions is important for CRF 1 R activation. Significance: This knowledge may aid in the development of nonpeptide CRF 1 R antagonists for use in stress-related disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…Similarly, Bortolato et al have recently suggested, as in class A GPCRs [53], a central hydrophobic core that could initiate class B receptor activation [42]. Furthermore, recent work in CRF 1 R suggested that secretin-like receptors shared a similar transmission switch as described for class A, involving positions 3.40 and 6.44 in TMs 3 and 6 [26]. These small local structural changes near the binding site are translated into largerscale helix movements at the intracellular site, mainly TMs 5 and 6, opening an intracellular cavity required for the binding of the Cterminal a5 helix of the G protein [18].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Similarly, Bortolato et al have recently suggested, as in class A GPCRs [53], a central hydrophobic core that could initiate class B receptor activation [42]. Furthermore, recent work in CRF 1 R suggested that secretin-like receptors shared a similar transmission switch as described for class A, involving positions 3.40 and 6.44 in TMs 3 and 6 [26]. These small local structural changes near the binding site are translated into largerscale helix movements at the intracellular site, mainly TMs 5 and 6, opening an intracellular cavity required for the binding of the Cterminal a5 helix of the G protein [18].…”
Section: Discussionmentioning
confidence: 84%
“…To compare these mechanisms within classes A and B, we use in this manuscript the Ballesteros and Weinstein general numbering scheme designed for class A GPCRs [25]. The correspondence between classes A and B is based on previously reported structure-based sequence alignment of all available crystal structures of GPCRs [12,26]. For easier comparison with previous Table 1 Effect of GIPR mutations on GIP-induced cAMP production, GIPR expression and 125 I-Phe 1 -GIP binding.…”
Section: Identification Of Putative Amino Acids and Motifs Involved Imentioning
confidence: 99%
“…Indeed, the CRF [1-16]/R1ΔN chimera was active in the absence of an exogenously administrated agonist (constitutively active receptor). Antalarmin binds to the TMs of the CRF [1-16]/R1ΔN chimera and blocks receptor activation [102]. In contrast, the constitutive activity of the CRF [1-16]/R1ΔN chimera was not blocked by astressin, which interacts with the N-domain of wild-type CRF1R [101].…”
Section: Two-domain Binding Model Of Ligand/receptor Interactionmentioning
confidence: 99%
“…For family B GPCRs, the conserved residues were numbered according to the Wootten numbering [130]. Although the receptors of families A and B are different, their overall fold is similar allowing the alignment of the sequences of receptors in both families based on their structures [102,121]. This alignment enabled us to use the Ballesteros-Weinstein general scheme to number TM residues of receptors of both families in this manuscript.…”
Section: Structural and Functional Characteristics Of The N-domain Anmentioning
confidence: 99%
See 1 more Smart Citation